IDENTIFIKASI AKAR PENYEBAB RISIKO OPERASIONAL TENAGA KERJA PADA UMKM BATIK VIRDES DI BANYUWANGI - Reza Triyuni Widiastuti; Alfian Hadi Nurrohman; Nadia Dwi Rahmawati; Sri Wulandari; Jemi Cahya Adi Wijaya (Jurnal Kajian dan Terapan Pariwisata, 2025)
Batik Virdes is a small and medium enterprise locate in Tampo Village, Cluring District, Banyuwangi Regency. Batik Virdes has been established since 1998, offering a variety of batik products range from fabric in meter sizes to finished goods such as clothing and batik headbands with distinctive motifs unique to Batik Virdes. Batik Virdes also produces various types of batik including stamped batik, batik prints, and handwritten batik. In addition to producing beneficial products, Batik Virdes also provide empowerment in maintaining business stability. However, empowerment often faces challenges related to operations because they also use a community empowerment system in recruiting labour. This research focuses on identifying the root causes of operational risks associated with labour in Batik Virdes. The technique used is a descriptive approach conducted through interviews and direct observation at the business location by compiling a risk classification table and visualizing it using a fishbone diagram. The research findings show that the application of community empowerment in the selection of employees at Batik Virdes is a strategic way because it can reduce costs and provide an overview of basic skills, as well as show the identification of the root causes of operational risks. With the identification of the root causes of existing risks, it is hoped that the owner can carry out mitigation to address the risks to support business continuity.